Photorefractive materials for dynamic optical recording : fundamentals, characterization and technology - Sochaczewsky, Jaime Frejlich, 1946- (John Wiley & Sons Inc., 2020)
"The book gives a comprehensive overview of the physics, technology and characterization of photorefractive materials that are used for optical recording, covering both transient and permanent holographic information storage methods. The clear presentation and explanation of the different methods allows the readers to easily find the most appropriate one for their respective needs"-- Provided by publisher
Keywords: Laser recording -- Materials.; Photorefractive materials.; elektronické knihy; electronic books